The GABAergic system contributes to the anxiolytic-like effect of essential oil from Cymbopogon citratus (lemongrass) - Rodrigues de Almeida Costa, Celso A. [UNESP]; Kohn, Daniele Oliveira [UNESP]; de Lima, Valeria Martins [UNESP]; Gargano, Andre Costa [UNESP]; Florio, Jorge Camilo; Costa, Mirtes [UNESP] (Elsevier B.V., 2011)
Ethnopharmacological relevance: The essential oil (EO) from Cymbopogon citratus (DC) Stapf is reported to have a wide range of biological activities and is widely used in traditional medicine as an infusion or decoction. However, despite this widely use, there are few controlled studies confirming its biological activity in central nervous system.Materials and methods: The anxiolytic-like activity of the EO was investigated in light/dark box (LDB) and marble-burying test (MBT) and the antidepressant activity was investigated in forced-swimming test (FST) in mice. Flumazenil, a competitive antagonist of benzodiazepine binding and the selective 5-HT1A receptor antagonist WAY100635 was used in experimental procedures to determine the action mechanism of EO. To exclude any false positive results in experimental procedures, mice were submitted to the rota-rod test. We also quantified some neurotransmitters at specific brain regions after EO oral acute treatment.Results: The present work found anxiolytic-like activity of the EO at the dose of 10 mg/kg in a LDB. Flumazenil, but not WAY100635, was able to reverse the effect of the EO in the LOB, indicating that the EO activity occurs via the GABA(A) receptor-benzodiazepine complex. Only at higher doses did the EO potentiate diethyl-ether-induced sleeping time in mice. In the FST and MBT, EO showed no effect. Finally, the increase in time spent in the light chamber, demonstrated by concomitant treatment with ineffective doses of diazepam (DZP) and the EO, revealed a synergistic effect of the two compounds. The lack of activity after long-term treatment in the LDB test might be related to tolerance induction, even in the DZP-treated group. Furthermore, there were no significant differences between groups after either acute or repeated treatments with the EO in the rota-rod test. Neurochemical evaluation showed no amendments in neurotransmitter levels evaluated in cortex, striatum, pons, and hypothalamus.Conclusions: The results corroborate the use of Cymbopogon citratus in folk medicine and suggest that the anxiolytic-like effect of its EO is mediated by the GABA(A) receptor-benzodiazepine complex. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Anxiolytic; Cymbopogon citratus; Essential oil; GABAergic system; Lemongrass; Sedative